2015
DOI: 10.3758/s13420-015-0195-9
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative properties of the reinforcer can be used to attenuate the renewal of extinguished operant behavior

Abstract: Previous research on the resurgence effect suggests that reinforcers that are presented during the extinction of an operant behavior can control inhibition of the response. To further test this hypothesis, three experiments with rat subjects examined the effectiveness of using reinforcers that were presented during extinction as a means of attenuating or inhibiting the operant renewal effect. In Experiment 1, lever pressing was reinforced in Context A, extinguished in Context B, and then tested in Context A. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
60
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 40 publications
14
60
1
Order By: Relevance
“…In that experiment, high and indistinguishable levels of resurgence were seen when animals received Phase-2 training on an FR 10, a yoked VI, or a yoked variable-time (VT) schedule. Similar results recently have been reported by Trask and Bouton (2015).…”
Section: Basic Features Of Resurgencesupporting
confidence: 93%
See 3 more Smart Citations
“…In that experiment, high and indistinguishable levels of resurgence were seen when animals received Phase-2 training on an FR 10, a yoked VI, or a yoked variable-time (VT) schedule. Similar results recently have been reported by Trask and Bouton (2015).…”
Section: Basic Features Of Resurgencesupporting
confidence: 93%
“…In addition, changing the qualitative properties of a reinforcer between Phase 2 and test (while keeping their rate constant) can also produce resurgence, suggesting that the discriminative function (rather than just the disrupting properties) of the reinforcer can play a crucial role (Bouton & Trask, 2015). Other experiments have demonstrated that a reinforcer specifically associated with the inhibition of an operant behavior can be used to inhibit behavior in renewal tests (Trask & Bouton, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O1 and O2 were provided by grain and sucrose food pellets (counterbalanced). Previous research in this laboratory has found these pellets to be discriminably different (Bouton, Todd, León, Miles, & Epstein, 2013; Bouton & Trask, 2015; Trask & Bouton, 2014; 2015), and they enter into separate associations with different Rs (Trask & Bouton, 2014). The new question was whether extinction of the response in S1 would still transfer to S2 when R had been associated with another outcome in that stimulus.…”
Section: Methodsmentioning
confidence: 90%